Vitals E-Medic Plus: An Open-Source Hardware (OSH) Derived Work Medical Device for A Cloud-based Patient Monitoring System - Sansolis, Evans; Damasco, Bob; Gabawa, Lea M. (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
This paper deals with the development of Vitals E-Medic Plus– an Open-source Hardware (OSH) derived work medical device built for a Cloud-based Patient Monitoring System. Vitals E-Medic Plus comprises two sets of open-source medical sensors: (1) open-source medical sensors for a patient’s vital sign monitoring and (2) open-source medical sensors for medical diagnostic tests. Vitals E-Medic Plus, medical sensors for patient’s vital sign monitoring include temperature, blood pressure, arterial oxygen saturation (SP02), heart and pulse rate, and respiratory rate. In contrast, open-source medical sensors for medical diagnostic tests include sensors for Capillary Blood Glucose (using glucometer), Electromyography (EMG), and Electrocardiogram (ECG/EKG). The two sets of open-source medical sensors were collectively organized and attached to an open-source Bio-Shield Platform atop NodeMCU System-on-chip module. Vitals E-Medic Plus device was developed under an Iterative Prototyping Engineering Design Methodology and employed Iterative Software Development Methodology for its software development. This device was tested and evaluated by Barangay Health Workers from the Philippines based on its efficiency, effectiveness, and reliability in gathering vital signs and diagnosing diabetes and heart diseases from a sizeable collection of patients during a one-day medical mission. One of the significant limitations of this device is, Vitals E-Medic Plus does not have any medical certifications. Thus, it cannot be used as a medical tool for monitoring critical patients who require accurate and precise monitoring or those whose medical conditions must be measured accurately and precisely for an undisclosed professional medical diagnosis.